Diversity of culturable thermophiles from hotsprings of Mid-China - Li, Y-X; Zhang, X-Q; Lin, Y-Y; Wang, Y; Wu, M (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2008)
The phylogenetic diversity of culturable thermophiles from hotsprings of Sichuan and Shanxi province was investigated. A total of 47 moderately thermophilic strains were isolated. Analysis of 16S rRNA gene sequences reveald that most of the isolates is thermophilic bacilli, which mainly belong to two genera, Anoxybacillus and Geobacillus. The majority of these thermophlies is able to secrete thermostable hydrolytic enzymes at 60 degree C or 70 degree C. Totally, 60% of the isolates can utilize Tween, 29% can secrete xylanase, the strains releasing protease or amylase occupy 38%, but no one can produce chitinase or chitosanases. Moreover, the difference of enzyme production is distinct either intraspecifically or interspecifically.